EFEKTIFITAS MODEL PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION (GI) PADA MATERI BARISAN DAN DERET DITINJAU DARI TIPE KEPRIBADIAN SISWA SMK KELAS X DI KABUPATEN KLATEN - Aji Permana Putra; Nuria Mahdra Fajarini; Nurni Utami (Intersections, 2020)
The objectives of this research were to find out on the topic of Sequences and Series: (1) which had better learning achievement among cooperative learning Group Investigation (GI) or a direct learning; (2) which had better learning achievement between melancholies students, phlegmatic students, sanguine students or choleric students; (3) at each personality types, which had better learning achievement among GI or direct learning, and (4) at each learning models, which had better learning achievement between melancholies students, phlegmatic students, sanguine students or choleric students. This research was a quasi-experimental with 2×4 factorial design. The population was all students in tenth grade of vocational schools technology, health, and agriculture in Klaten Regency on Academic Years 2019/2020. Sampling was done by stratified cluster random sampling technique. The total of sample was 80 students. Statistical tests using the method Lilliefors test for normality, homogeniety of the Bartlett method, anava test with F test (Fisher) and post hoc test using the Scheffe’ method. The significance level was 0,05. Based on hypothesis test, it could be concluded as follows: (1) GI had better learning achievement than direct learning,; (2) there were no any differences in the learning achievement in mathematics of the students with melancholies, phlegmatic, sanguine or choleric personality types; (3) in each personality types, the cooperative learning model GI had better than cooperative learning Jigsaw II direct learning model; (4) in each learning model, the students with melancholies, phlegmatic, sanguine or choleric personality types have the same learning achievement